Interactions between immune response to fungal infection and microRNAs: The pioneer tuners. Issue 1 (19th November 2019) - Pakshir, Keyvan; Badali, Hamid; Nami, Sanam; Mirzaei, Hamed; Ebrahimzadeh, Veghar; Morovati, Hamid
Summary: Due to their physiological and biological characteristics, numerous fungi are potentially emerging pathogens. Active dynamicity of fungal pathogens causes life‐threatening infections annually impose high costs to the health systems. Although immune responses play crucial roles in controlling the fate of fungal infections, immunocompromised patients are at high risk with high mortality. Tuning the immune response against fungal infections might be an effective strategy for controlling and reducing the pathological damages. MicroRNAs (miRNAs) are known as the master regulators of immune response. These single‐stranded tuners (18‐23 bp non‐coding RNAs) are endogenously expressed by all metazoan eukaryotes and have emerged as the master gene expression controllers of at least 30% human genes. In this review article, following the review of biology and physiology (biogenesis and mechanism of actions) of miRNAs and immune response against fungal infections, the interactions between them were scrutinised. In conclusion, miRNAs might be considered as one of the potential goals in immunotherapy for fungal infections. Undoubtedly, advanced studies in this field, further identifying of miRNA roles in governing the immune response, pave the way for inclusion of miRNA‐related immunotherapeutic in the treatment of life‐threatening fungal infections.